Gambaran Pengetahuan Wanita Usia Subur Tentang PAP Smear di Poliklinik Kebidanan RSUD Sanjiwani Gianyar - Jayantari, Anak Agung Istri Hendri Dwi; Purnamayanti, Ni Made Dwi (JURNAL KEBIDANAN, 2024)
Cervical cancer is a malignant tumor that grows in the cervix that is detected early by the pap smear method. Pap smear examination has an accuracy in diagnosing up to 98% and has a specificity of 93%. This study aims to determine the description of knowledge of women of childbearing age about pap smears at the Obstetrics Polyclinic of Sanjiwani Hospital. Descriptive research design, Cross Sectional research design with a sample size of 107 respondents. The sampling technique used purposive sampling. This research data is primary data using a questionnaire instrument. The research was conducted from February 16 to March 31, 2024. Data analysis used in this study was univariate analysis. The results showed that 72% had good knowledge about the benefits of pap smears, 21.5% had good knowledge about indications of pap smears, 31.8% had good knowledge about contraindications to pap smears, 37.4% had good knowledge about preparation before pap smears, and as many as 22,4% had good knowledge about pap smears. The conclusion of the results showed that a small proportion of respondents had good knowledge about pap smears. Midwives at Sanjiwani Hospital should increase the frequency of education to the community with booklets, posters, or educational videos.